Analisis Butir Soal Tipe Multiple Choice Ujian Akhir Semester Ganjil Kelas X Tahun Ajaran 2022/2023 Mata Pelajaran Pendidikan Agama Islam di SMA Negeri 1 Padang - Muhamad Rishan; Sulaiman Sulaiman (ISLAMIKA, 2023)
This research aims to determine the quality of multiple-choice items in the Odd Semester Final Exam for the 2022/2023 academic year of Islamic Education subject in SMA Negeri 1 Padang, focusing on the aspects of difficulty level, discrimination power, and distractor quality. This study employs a descriptive research design with a quantitative approach. The sample used in this research consists of 420 students, which represents the entire population, using a total sampling technique. The data collection method utilized in this study is documentation. The data analysis technique employed is ANATES version 4. Based on the difficulty level calculation using ANATES version 4, the results showed that out of 50 items, 3 items (6%) were classified as difficult, 12 items (24%) as moderate, and 35 items (70%) as easy. Regarding the discrimination analysis using ANATES version 4, out of 50 items, 18 items (36%) were categorized as poor, 17 items (34%) as fair, 14 items (28%) as good, no items were categorized as very good, and 1 item (2%) was categorized as a negative item, which indicates the need for removal or replacement. Lastly, based on the analysis of distractor quality, 15 items (30%) were found to have effective distractors, while 35 items (70%) had ineffective distractors.